EFL Students’ Reliance on ChatGPT as Writing Support: A Study on Thesis Writing at Hamzanwadi University - Muhammad Jihadul Khairi Rizki; Siti Maysuroh; Laila Wati; Ari Prasetyaningrum (Mataram University, 2026)
The research investigates the use of ChatGPT by EFL learners for their thesis writing in Hamzanwadi University. A sequential explanatory mixed-methods design was utilized whereby quantitative data were collected through questionnaires from 55 participants who are in the eighth semester while qualitative data were obtained from semi-structured interviews conducted with five purposive respondents. The study results showed a high level of functional reliance on ChatGPT with respect to the ability to understand certain complex theories, improve the grammar, and write paragraphs among students. Yet, psychological and cognitive dependence of students were at moderate levels. Hence, students are able to retain their critical thinking abilities and independence in academic pursuits and consider AI as their cooperating language helper rather than cognitive worker's replacement. Such a phenomenon that may be called